Optimization of individualized graft composition: CD3/CD19 depletion combined with CD34 selection for haploidentical transplantation. Issue 9 (27th June 2016) - Huenecke, Sabine; Bremm, Melanie; Cappel, Claudia; Esser, Ruth; Quaiser, Andrea; Bonig, Halvard; Jarisch, Andrea; Soerensen, Jan; Klingebiel, Thomas; Bader, Peter; Koehl, Ulrike
Abstract : BACKGROUND: Excessive T‐cell depletion (TCD) is a prerequisite for graft manufacturing in haploidentical stem cell (SC) transplantation by using either CD34 selection or direct TCD such as CD3/CD19 depletion. STUDY DESIGN AND METHODS: To optimize graft composition we compared 1) direct or indirect TCD only, 2) a combination of CD3/CD19‐depleted with CD34‐selected grafts, or 3) TCD twice for depletion improvement based on our 10‐year experience with 320 separations in graft manufacturing and quality control. RESULTS: SC recovery was significantly higher (85%, n = 187 vs. 73%, n = 115; p < 0.0001), but TCD was inferior (median log depletion, −3.6 vs. −5.2) for CD3/CD19 depletion compared to CD34 selection, respectively. For end products with less than −2.5 log TCD, a second depletion step led to a successful improvement in TCD. Thawing of grafts showed a high viability and recovery of SCs, but low NK‐cell yield. To optimize individualized graft engineering, a calculator was developed to estimate the results of the final graft based on the content of CD34+ and CD3+ cells in the leukapheresis product. CONCLUSION: Finally, calculated splitting of the starting product followed by CD3/19 depletion together with CD34+ graft manipulation may enable the composition of optimized grafts with high CD34+‐cell and minimal T‐cell content.